(untitled) (Revista de Ciências Agroveterinárias, 2016)
This study aimed to evaluate nutrient content on leaves and fruit flesh, yield and quality of fruits, as well as apple tree growth as affected by the fertilizer physical form (conventional or fertirrigation) and water addition or not via irrigation. The experiment was carried out in São Joaquim, Southern of Brazil, during the 2012/2013 and 2013/2014 growing season. The orchard was planted in 2011 with ‘Kinkas’ cultivar grafted over a Marubakaido rootstock, 1.666 trees ha-1. The eight replications of each treatment were allocated in the completely randomized block design. Treatments consisted of conventional solid soil fertilization (T1), irrigation + conventional solid soil fertilization (T2), irrigation + fertirrigation (T3), and fertirrigation (T4). From the daily averages of tensiometer readings in addition to the water soil retention the irrigation needs and the application time curve were determined. In 2012, 27 kg ha-1 of N was applied; in the following season, it 100 kg ha-1 of N and 150 kg ha-1 of K2O was applied. Fertilizers were split three times on treatments T1 and T2, and six times on treatments T3 and T4, from November through January. During the experimental period it many drought periods were observed. Irrigation and fertirrigation had no effect on initial apple tree growth. Irrigation did not affect the nutrient content in leaves or fruit flesh. Fruits from the T1 treatment had higher firmness than fruits from the other treatments. Fruits from T3 (irrigation + fertirrigation) presented the highest weight. Fruit yield, however, did not differ among treatments. Fertirrigation was the best form of nutrient application to the plants, but it is necessary to determine rates and times of application to obtain the maximum productive efficiency.